Development of novel diagnostic system for pancreatic cancer, including early stages, measuring mRNA of whole blood cells. Issue 4 (27th March 2019) - Sakai, Yoshio; Honda, Masao; Matsui, Shigeyuki; Komori, Osamu; Murayama, Toshinori; Fujiwara, Tadami; Mizuno, Masaaki; Imai, Yasuhito; Yoshimura, Kenichi; Nasti, Alessandro; Wada, Takashi; Iida, Noriho; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is the most life‐threating disease among all digestive system malignancies. We developed a blood mRNA PDAC screening system using real‐time detection PCR to detect the expression of 56 genes, to discriminate PDAC from noncancer subjects. We undertook a clinical study to assess the performance of the developed system. We collected whole blood RNA from 53 PDAC patients, 102 noncancer subjects, 22 patients with chronic pancreatitis, and 23 patients with intraductal papillary mucinous neoplasms in a per protocol analysis. The sensitivity of the system for PDAC diagnosis was 73.6% (95% confidence interval, 59.7%‐84.7%). The specificity for noncancer volunteers, chronic pancreatitis, and patients with intraductal papillary mucinous neoplasms was 64.7% (54.6%‐73.9%), 63.6% (40.7%‐82.8%), and 47.8% (26.8%‐69.4%), respectively. Importantly, the sensitivity of this system for both stage I and stage II PDAC was 78.6% (57.1%‐100%), suggesting that detection of PDAC by the system is not dependent on the stage of PDAC. These results indicated that the screening system, relying on assessment of changes in mRNA expression in blood cells, is a viable alternative screening strategy for PDAC. Abstract : Development of a blood mRNA pancreatic ductal adenocarcinoma (PDAC) screening system using real‐time detection PCR in order to discriminate PDAC patients from healthy volunteers. We performed an investigator‐initiated clinical study to assess the performance of the developed system. The sensitivity of the system for PDAC diagnosis and the specificity for non‐cancer volunteers were determined for the evaluation of the screening system.